ANALISIS PENGARUH DESAIN PRODUK, KUALITAS PRODUK, HARGA KOMPETITIF, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Pelanggan Nesty Collection Jakarta) - Reven, Daniel; Ferdinand, Augusty Tae (Diponegoro Journal of Management, 2017)
The gradual increase of human population in Indonesia caused the increasing of the primary need of clothing, resulted in the development of fashion businesses in Indonesia, especially in the DKI Jakarta as the Capital Region of Indonesia. Nesty Collection is a private label brand fashion firm that competes with the other private label fashion firms in Tanah Abang Trading Center to earn large profits from fashion marketing. This study aimed to analyze the factors that might affect the purchasing decision of Nesty Collection’s fashion products. This study used five variables, which are product design, product quality, competitive price, brand image, and purchase decision. This research hypothesis testing using the data of 102 respondents. The analysis technique used in this research is to use a software program Statistical Package for Social Science (SPSS) 22. Results showed that the purchasing decision of Nesty Collection’s fashion products was affected by brand image and competitive price. Brand image of Nesty Collection was affected by product design and product quality.